Technology and engagement : making technology work for first-generation college students - Rowan-Kenyon, Heather T., 1973-; Martínez Alemán, Ana M.; Savitz-Romer, Mandy (Rutgers University Press, 2018)
"Technology and Engagement is based on a four-year study of how first generation college students use social media, aimed at improving their transition to and engagement with their university. Through web technology, including social media sites, students were better able to maintain close ties with family and friends from home, as well as engage more with social and academic programs at their university. This 'ecology of transition' was important in keeping the students focused on why they were in college, and helped them become more integrated into the university setting. By showing the gains in campus capital these first-generation college students obtained through social media, the authors offer concrete suggestions for how other universities and college-retention programs can utilize the findings to increase their own retention of first-generation college students"--